A tomada de decisão apoiada e seus sujeitos - Couto, Letícia Ferreira (2020)
This paper aims to understand or institute a legal procedure for the supported decision making and its subjects, and to have understanding of its concept, performance and what are the legal issues that are attributed to its subjects, will be analyzed or processed historical-evolutionary practices that enabled its emergence, demonstrating all the perspectives through which they integrate or order civil life. Seizes as effective modifications that the Law on the Inclusion of Persons with Disabilities (Statute of Persons with Disabilities) introduced the Civil Code of 2002 with the aim of reaffirming the dignity of the human person, modifying a “theory of disabilities”, conferring those suffering some disability, a presumption of ability. This research reflects as effective changes in the application of civil law by the analysis of the application and application of these modified devices. It will explain the problems of the Code of Civil Procedure and the revocation of provisions amended in the Civil Code by the Statute of the Disabled, listing the guidelines and solutions for the best application of the institute in Brazilian law. These transformations were created for the creation of Supported Decision Making, or the third kind of support in force in our order, an instrument that represents the exercise of private capacity through civil liberties linked to persons with disabilities or detention of any vulnerability. It will make comparisons with other support models around the world, including with related Brazilian institutes, to verify as peculiarities of this new and intermediate cooperation support for the exercise of individual capacity, and how to impact its considered subject members or current legal system